Roles of enhanced ITZ in improving the mechanical properties of concrete prepared with different types of recycled aggregates. (15th November 2022) - Liu, Yi; Ren, Pengfei; Garcia-Troncoso, Natividad; Mo, Kim Hung; Ling, Tung-Chai
Abstract: Recycled aggregates (RAs) derived from construction and demolition (C&D) waste usually contain several types of aggregates (e.g. recycled concrete aggregate (RCA), recycled concrete block aggregate (RCBA), and recycled red brick aggregate (RBA)). The physical properties of these RAs with diverse intrinsic strength and water absorption could affect the interfacial transition zone (ITZ) and mechanical properties of a new concrete differently. This paper aims to study the compressive strength and tensile bond strength of concrete made with full natural aggregate (NA) substitute by RCA, RCBA and RBA. Microhardness testing and scanning electron microscope-backscattered electron (SEM-BSE) image analysis were used to elucidate the microstructural performance within the ITZ and its underlying mechanism. Experimental results showed that both RCA and RCBA concrete had a higher compressive strength than NA concrete despite the weaker intrinsic RAs properties. In terms of tensile bond strength, all RAs concretes exhibited better tensile bond strength (5–49%) than NA concrete. It appears that the beneficial effect of enhanced ITZ outweighed the intrinsic properties of the RAs with regards to the concrete performance. This was further confirmed by the microhardness and BSE results as all concretes with the RAs exhibited higher microhardness value and lower porosity than NA concrete. Graphical abstract: Image 1 Highlights: RCA and RCBA concrete had higher compressive strength than NA concrete due to enhanced ITZ. RCA and RCBA samples showed 22–49% higher tensile bond strength than NA samples. The new ITZ in RAs concrete had higher microhardness and lower porosity. RAs induced stronger interlocking between aggregate and new cementitious matrix.